IL1β inhibits differentiation of cementoblasts via microRNA‐325‐3p. Issue 3 (3rd November 2019) - Wang, Yuzhuo; Li, Ying; Shao, Pu; Wang, Liuyi; Bao, Xingfu; Hu, Min
Abstract: Cementum regeneration is considered the gold standard for the treatment of periodontitis. As one of the most important primary proinflammatory cytokines, interleukin 1β (IL1β) plays an essential role during the early stage of periodontitis and its amounts simultaneously increase dramatically during this stage. Though promising, the differentiation of cementoblasts upon IL1β‐induced inflammation of the microenvironment and the relative interaction mechanism are still unknown. Here, we found that IL1β inhibited cementoblast differentiation and microRNA‐325‐3p (miR‐325‐3p) was increased during IL1β‐stimulated cementoblasts. Bioinformatics analysis and luciferase reporter assay demonstrated miR‐325‐3p targeted runt‐related transcription factor 2 directly. Transfection of miR‐325‐3p suppressed cementoblast differentiation in vitro and the formation of cementum‐like tissues in vivo. The inhibitor of miR‐325‐3p could mitigate the above effects induced by IL1β. Accordingly, our finding suggests a critical role of miR‐325‐3p in linking inflammation to impaired cementum regeneration and provides a potential possibility for applying miR‐325‐3p inhibitors in the treatment of periodontitis‐related bone loss. Abstract : Interleukin 1β (IL1β) plays an essential role in periodontal disease. IL1β inhibited the differentiation of cementoblasts via activating miR‐325‐3p expression. Applying miR‐325‐3p inhibitors provided therapy in cementum loss caused by periodontitis.